If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + -5) = 3(6x + 1) Reorder the terms: 6(-5 + 3x) = 3(6x + 1) (-5 * 6 + 3x * 6) = 3(6x + 1) (-30 + 18x) = 3(6x + 1) Reorder the terms: -30 + 18x = 3(1 + 6x) -30 + 18x = (1 * 3 + 6x * 3) -30 + 18x = (3 + 18x) Add '-18x' to each side of the equation. -30 + 18x + -18x = 3 + 18x + -18x Combine like terms: 18x + -18x = 0 -30 + 0 = 3 + 18x + -18x -30 = 3 + 18x + -18x Combine like terms: 18x + -18x = 0 -30 = 3 + 0 -30 = 3 Solving -30 = 3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2x^2+35x+27=0 | | 24/.15 | | (3tan^-1(3/4y))^2 | | 4/7b-3=12 | | m=4m+4w | | 5a-3a=1+205 | | 2-k/-7=11 | | 11(v+4)-2v=3(3v+4)-15 | | 66=x+(2x+3) | | f(x)=x^2-7x+4 | | (3x)x=320 | | 8.3+9x=8.5 | | 2(16+y)-8+5y=16 | | 5-4y+y-1=-22 | | 2(x-5)=6-(x+7)-3 | | 4+7=95 | | p=12-2D | | (5x-2)x=18 | | h(2h+5)=52 | | P=12-2Qd | | -6n+8=-4n+10 | | 10y-3= | | -5(n-5)-(3n-1)=-3+(6n-6) | | x^2+44=188 | | 10y-3=97-2x | | 66=x+(.5x+3) | | 9/10*2/4 | | 5x-2*-5=30 | | 3(x-4)-7(x+4)=-2(x+12) | | 9/19*2/4 | | (5*-6)+30=y | | abs(z-5-3i)=3 |